FLOOD HAZARD MAPPING BASED ON MULTI-CRITERIA SPATIAL ANALYSIS IN THE SAMIN WATERSHED, INDONESIA - Sofyan Sholeh; Chatarina Muryani; Suryanto Suryanto (GeoEco, 2024)
The Samin watershed which is located in the Mount Lawu area is vulnerable to flood disasters due to human activities. This research was carried out by inventorying parameter data to create a flood disaster vulnerability map using a GIS-based multi-criteria spatial approach. The seven parameters used in flood disaster analysis are Elevation, Slope, Distance from River, Drainage density, Topographic Wetness Index (TWI), Landuse, Rainfall, Type of Soil, Geology. The weight of each parameter is determined using the Analytical Hierarchy Process (AHP) which has the driving factors for flood disasters. The flood hazard map was obtained using a weighted overlay method and grouped into five classes, namely very low, low, medium, high and very high. The results of the analysis show that 11.36% of the study area has a very low hazard, 27.10% has a low hazard, 39.57% has a medium hazard, 20.43% has a high hazard and 1.54% has a very high hazard.